Sleep in Older Adults and Its Possible Relations With COVID-19 - Pires, Gabriel Natan; Ishikura, Isabela Antunes; Xavier, Sandra Doria; Petrella, Caetano; Piovezan, Ronaldo Delmonte; Xerfan, Ellen Maria Sampaio; Andersen, Monica Levy; Tufik, Sergio (Frontiers in Aging Neuroscience, 2021)
Since the beginning of the COVID-19 pandemic, older adults have been reported as a highly vulnerable group, encompassing a higher prevalence of severe cases and of negative outcomes. Research has focused on the reasons why older adults are at greater risk. Sleep pattern across lifespan undergo marked modifications and a specific sleep profile can be observed in older adults, encompassing advanced sleep timing, a morningness preference, longer sleep-onset latency, shorter overall sleep duration, increased sleep fragmentation, reduced slow-wave sleep and increased wake time after sleep onset. Additionally, increased prevalence of sleep disorders can be observed, such as obstructive sleep apnea and insomnia. Previous research has already correlated sleep disorders (especially sleep apnea) with COVID-19, but few studies have focused specifically on the older population. We believe that the intrinsic sleep pattern of older adults and the main sleep disorders in this population might be an important factor in understating why they are at a greater risk of negative outcomes of COVID-19. In this review we discussed the relationship between sleep and COVID-19 among older adults, focusing in three different aspects: 1. Sleep-related issues that might increase the likelihood of getting infected by SARS-COV-2; 2. Sleep disturbances that might increase the predisposition to worse COVID-19 prognosis and outcomes; and 3. COVID-19-related aspects affecting community-dwelling older adults (social isolation, quarantine, home confinement, etc) that may impact sleep.